2014
DOI: 10.1093/nar/gku186
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the 5hmC specific endonuclease PvuRts1I

Abstract: PvuRts1I is a prototype for a larger family of restriction endonucleases that cleave DNA containing 5-hydroxymethylcytosine (5hmC) or 5-glucosylhydroxymethylcytosine (5ghmC), but not 5-methylcytosine (5mC) or cytosine. Here, we report a crystal structure of the enzyme at 2.35 Å resolution. Although the protein has been crystallized in the absence of DNA, the structure is very informative. It shows that PvuRts1I consists of an N-terminal, atypical PD-(D/E)XK catalytic domain and a C-terminal SRA domain that mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…However, these homologues may have evolved different substrate activities that may assist in survival in the wake of infection by T4-like phages . During the course of our study, Kazrani and coworkers reported the crystal structure of PvuRts1I (Kazrani et al, 2014). These two structure are very similar (with an r.m.s.d.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, these homologues may have evolved different substrate activities that may assist in survival in the wake of infection by T4-like phages . During the course of our study, Kazrani and coworkers reported the crystal structure of PvuRts1I (Kazrani et al, 2014). These two structure are very similar (with an r.m.s.d.…”
Section: Discussionmentioning
confidence: 61%
“…3). Although Kazrani et al (2014) claimed that the predicted dimer could not be found in their crystal, which belonged to space group P4 1 2 1 2, we considered that the dimer in our space group P4 3 2 1 2 crystal is a productive one. The PvuRts1I dimer interface is mediated by the Nterminal endonuclease domain, and the two SRA-like domains are located on opposite sides of the dimer (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…There is much interest in understanding where these forms occur in genomes, how they differ between cell types and change with time and circumstances and how they affect gene expression. Recently discovered ‘modification-dependent’ restriction enzymes such as MspJI/AspBHI ( 8 , 9 ), and PvuRts1I/AbaSI ( 10 , 11 ), provide a way of answering some of these questions at single-base resolution. These enzymes bind to duplex DNA at sequences containing certain modifications and cleave the DNA a short distance away, generating fragments that can be sequenced and analyzed by bioinformatics ( 7 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…These include MspJI, which recognizes 5mC and 5hmC (20), the PvuRts1I family, whose members show unique individual specificities for 5hmC and/or 5-glucosylhydroxymethylcytosine (5ghmC) (21), and GmrSD, which recognizes 5ghmC (22). Structural studies of McrB, MspJI, PvuRtsI, and AbaSI suggest type IV systems employ a generalized base-flipping mechanism for recognition of the modified DNA (23)(24)(25)(26)(27).…”
Section: This Work Was Supported By Cornell University and National Imentioning
confidence: 99%